Correction: The oxygen-resistant [FeFe]-hydrogenase CbA5H harbors an unknown radical signal. Issue 29 (14th July 2022) - Heghmanns, Melanie; Rutz, Andreas; Kutin, Yury; Engelbrecht, Vera; Winkler, Martin; Happe, Thomas; Kasanmascheff, Müge
Abstract : Correction for 'The oxygen-resistant [FeFe]-hydrogenase CbA5H harbors an unknown radical signal' by Melanie Heghmanns et al., Chem. Sci., 2022, 13, 7289–7294, ; https://doi.org/10.1039/D2SC00385F .